2015
DOI: 10.1007/s00125-015-3734-1
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells infiltrate pancreatic islets in human type 1 diabetes

Abstract: Aims/hypothesis Beta cell destruction in human type 1 diabetes occurs through the interplay of genetic and environmental factors, and is mediated by immune cell infiltration of pancreatic islets. In this study, we explored the role of mast cells as an additional agent in the pathogenesis of type 1 diabetes insulitis. Methods Pancreatic tissue from donors without diabetes and with type 1 and 2 diabetes was studied using different microscopy techniques to identify islet-infiltrating cells. The direct effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 45 publications
5
51
0
Order By: Relevance
“…its endocrine as well as non-endocrine components) could be inflamed. A similar concept has also emerged in the type 1 diabetes pancreas scenario [10,25].…”
Section: Immune Cell Infiltration Of Pancreatic Islets In Type 2 Diabmentioning
confidence: 78%
See 4 more Smart Citations
“…its endocrine as well as non-endocrine components) could be inflamed. A similar concept has also emerged in the type 1 diabetes pancreas scenario [10,25].…”
Section: Immune Cell Infiltration Of Pancreatic Islets In Type 2 Diabmentioning
confidence: 78%
“…The authors identified cases with (n = 20) or without (n = 20) islet amyloid deposition, and demonstrated a significantly greater (approximately threefold) CD68 + cell infiltration in amyloidladen islets, which correlated with the severity of amyloid deposition. In a later study, Martino et al evaluated pancreatic tissue samples from organ donors (seven without diabetes, six with type 1 diabetes and seven with type 2 diabetes) by using different microscopy techniques (including electron microscopy) to identify islet-infiltrating cells [10]. The authors confirmed a greater islet infiltration by macrophages in the type 2 diabetic sections.…”
Section: Immune Cell Infiltration Of Pancreatic Islets In Type 2 Diabmentioning
confidence: 99%
See 3 more Smart Citations